Cat flea (Ctenocephalides felis) infestation in quarantined marsh deer (Blastocerus dichotomus) populations. - Szabó, M. P. [UNESP]; Matushima, E. R. [UNESP]; Pereira, M. D. [UNESP]; Werther, K. [UNESP]; Duarte, J. M. [UNESP] (American Association of Zoo Veterinarians, 2000)
Marsh deer (Blastocerus dichotomus) were captured for a research program in Brazil and maintained in quarantine stations. After 60 days, fleas were detected on animals and identified as Ctenocephalides felis felis. Elimination of the infestation was difficult. Animal treatment with a fipronil-based compound was effective, and subsequently captured animals were treated prophylactically. Some animals remained infested, and some died from the infestation.